The Neural Mechanisms of Tinnitus: A Perspective From Functional Magnetic Resonance Imaging - Hu, Jinghua; Cui, Jinluan; Xu, Jin-Jing; Yin, Xindao; Wu, Yuanqing; Qi, Jianwei (Frontiers in Neuroscience, 2021)
Tinnitus refers to sound perception in the absence of external sound stimulus. It has become a worldwide problem affecting all age groups especially the elderly. Tinnitus often accompanies hearing loss and some mood disorders like depression and anxiety. The comprehensive adverse effects of tinnitus on people determine the severity of tinnitus. Understanding the mechanisms of tinnitus and related discomfort may be beneficial to the prevention and treatment, then getting patients out of tinnitus distress. Functional magnetic resonance imaging (fMRI) is a powerful technique for characterizing the intrinsic brain activity and making us a better understand of the tinnitus neural mechanism. In this article, we review fMRI studies published in recent years on the neuroimaging mechanisms of tinnitus. The results have revealed various neural network alterations in tinnitus patients, including auditory system, limbic system, default mode network, attention system and some other areas involved in memory, emotion, attention and control. Moreover, changes of functional connectivity and neural activity in these networks are related to the perception, persistence and severity of tinnitus. In summary, the neural mechanism of tinnitus is a complex regulatory mechanism involving multiple networks. Future research is needed to study these neural networks more accurately to refine the tinnitus models.